2018
DOI: 10.1074/jbc.ra118.004028
|View full text |Cite
|
Sign up to set email alerts
|

CARM1-mediated methylation of protein arginine methyltransferase 5 represses human γ-globin gene expression in erythroleukemia cells

Abstract: Protein arginine methyltransferase 5 (PRMT5) is a member of the arginine methyltransferase protein family that critically mediates the symmetric dimethylation of Arg-3 at histone H4 (H4R3me2s) and is involved in many key cellular processes, including hematopoiesis. However, the post-translational modifications (PTMs) of PRMT5 that may affect its biological functions remain less well-understood. In this study, using MS analyses, we found that PRMT5 itself is methylated in human erythroleukemia Lys-562 cells. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…LKB1, a kinase with tumor suppressor function, phosphorylates multiple threonines (T132, 139 and 144) in the PRMT5 TIM-barrel domains required for MEP50, pICln and RIOK1 interaction, suppressing PRMT5 enzymatic activity [118]. PRMT5 itself is arginine-methylated by CARM1 (PRMT4) in the erythroleukemia cells Lys-562, which is essential for PRMT5 methyltransferase activity to repress human γ-globin expression via H4R3me2s [119]. Moreover, PRMT5 adaptors are subject to modifications that impact overall PRMT5 activity.…”
Section: Regulation By Ptmmentioning
confidence: 99%
“…LKB1, a kinase with tumor suppressor function, phosphorylates multiple threonines (T132, 139 and 144) in the PRMT5 TIM-barrel domains required for MEP50, pICln and RIOK1 interaction, suppressing PRMT5 enzymatic activity [118]. PRMT5 itself is arginine-methylated by CARM1 (PRMT4) in the erythroleukemia cells Lys-562, which is essential for PRMT5 methyltransferase activity to repress human γ-globin expression via H4R3me2s [119]. Moreover, PRMT5 adaptors are subject to modifications that impact overall PRMT5 activity.…”
Section: Regulation By Ptmmentioning
confidence: 99%
“…In contrast, JAK2V617F [ 42 ], a constitutive active mutant of Janus kinase 2 (JAK2) that is found in patients with myeloproliferative neoplasms, phosphorylates PRMT5 and downregulates its activity [ 43 ]. Furthermore, another member of the PRMT family, PRMT4, methylates PRMT5 and downregulates its activity [ 44 ]. It has also been reported that casein kinase 1 (CK1)-mediated PRMT1 phosphorylation regulates its specificity of chromatin binding [ 45 ], and that p38 mitogen-activated kinase (MAPK)-mediated PRMT4 phosphorylation regulates its localization [ 46 ].…”
Section: Prmtsmentioning
confidence: 99%
“…Because the roles of these additional methylations have not yet been defined, it would be interesting to understand the roles of other arginine residues that are methylated by PRMT5. Recently, it was reported that PRMT4 regulates PRMT5 activity [ 44 ]. Therefore, PRMT4 may be also involved in the regulation of GLI1 activity.…”
Section: Outlook For Prmt-mediated Gli1 Regulatory Mechanismsmentioning
confidence: 99%
“…In contrast, JAK2V617F [41], a constitutive active mutant of Janus kinase 2 (JAK2) that is found in patients with myeloproliferative neoplasms, phosphorylates PRMT5 and downregulates its activity [42]. Furthermore, another member of the PRMT family, PRMT4, methylates PRMT5 and downregulates its activity [43]. It has also been reported that casein kinase 1 (CK1)-mediated PRMT1 methylation regulates its specificity of chromatin binding, and that p38 mitogen-activated kinase (MAPK)-mediated PRMT4 phosphorylation regulates its localization.…”
Section: Regulation Of Prmt Activity By Post-translational Modificationsmentioning
confidence: 99%
“…Because the roles of these additional methylations have not yet been defined, it would be interesting to understand the roles of other arginine residues that are methylated by PRMT5. Recently, it was reported that PRMT4 regulates PRMT5 activity [43]. Therefore, PRMT4 may be also involved in the regulation of GLI1 activity.…”
Section: Outlook For Prmt-mediated Gli1 Regulatory Mechanismsmentioning
confidence: 99%